Neonatal Jaundice Causal Factors: A Literature Review - Pariqa Annisa; Andari Wuri Astuti; Surabhi Sharma (Women, Midwives and Midwifery, 2023)
Background: Jaundice (neonatal icterus), known as yellowish baby is a condition where the yellowing of the skin and sclera in newborns, due to increased levels of bilirubin in the blood (hyperbilirubinemia) which subsequently causes an increase in bilirubin in the fluid outside the cell (extracellular fluid). Jaundice is one of the contributors to infant morbidity in Indonesia because it can cause the baby's body to become limp, unwilling to suck, increased muscle tone, stiff neck, muscle spasms, convulsions, sensory disturbances, mental retardation, disability, and even death. Objective: This study aimed to review the evidence related to the factors causing jaundice in neonates. Method: This research method was a literature review study. Journal searches were carried out by applying online database such as ScienceDirect and PubMed. Author also used google scholar for search engine. The inclusion criteria in this study were journals published in 2015-2020 using Indonesian and English and full text. Journal search results obtained as many as 10 journals were reviewed in this study. Results: Birth weight of the baby, gestational age, asphyxia, infection, length of labor, frequency and sex are factors that cause jaundice while primiparous mothers are factors that do not cause jaundice. Based on the results of the review of the article the researchers found that there were gaps in the study this is research on the factors causing the occurrence of jaundice more focused on health problems of birth weight of the baby, gestational age, asphyxia, and infection, duration of delivery, frequency and sex. Only few researches are examining the factors associated with factors causing jaundice in neonates. Conclusion: The factors causing the occurrence neonatal jaundice are more focused on health problems of birth weight of babies, gestational age, asphyxia, infection, length of labor, frequency and sex. There are still few studies that examine the factors associated with factors that cause jaundice in neonates.